1965
DOI: 10.1126/science.149.3688.1113
|View full text |Cite
|
Sign up to set email alerts
|

Color-Discrimination Performance of Pigeons: Effects of Reward

Abstract: Performance of two pigeons given tasks in discriminating colors was examined on trials before and after they had occasionally received rewards for pecking when exposed to light of specific wavelengths. After a reward, the probability that the birds would respond to light svtimuli that were never rewarded was higher than before the reward was given, but paradoxically the birds showed no general decline in their ability to differentiate between stimuli at wavelengths 1 millimicron apart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Rilling and McDiarmid (1965) considered the behavior of pigeons discriminating between the number of pecks for two fixed-ratio schedules to be amenable to signal-detection analysis. Blough (1967) constructed ROCs based on the stimulus generalization data of pigeons for visual stimuli of different wavelengths, and Nevin (1965) pointed out the usefulness of SDT in interpreting the data of Boneau, Holland, and Baker (1965), who also examined wavelength discrimination by pigeons. By manipulating response outcomes, Stubbs (1968) produced changes in the relative frequencies of two responses emitted by pigeons discriminating the duration of a visual stimulus.…”
mentioning
confidence: 99%
“…Rilling and McDiarmid (1965) considered the behavior of pigeons discriminating between the number of pecks for two fixed-ratio schedules to be amenable to signal-detection analysis. Blough (1967) constructed ROCs based on the stimulus generalization data of pigeons for visual stimuli of different wavelengths, and Nevin (1965) pointed out the usefulness of SDT in interpreting the data of Boneau, Holland, and Baker (1965), who also examined wavelength discrimination by pigeons. By manipulating response outcomes, Stubbs (1968) produced changes in the relative frequencies of two responses emitted by pigeons discriminating the duration of a visual stimulus.…”
mentioning
confidence: 99%
“…The interactions of wavelength discrimination and reinforcement (Boneau, Holland, and Baker, 1965) have been examined within a detection-theory framework (Nevin, 1965), and a full-blown decision theory of animal discrimination performance has been published (Boneau and Cole, 1967). Blough (1967) has used signal-detection analysis to present wavelength generalization gradients in a novel way, and Rilling and McDiarmid (1965) and Stubbs (1968) …”
mentioning
confidence: 99%
“…Boneau et al (1965) showed that, at the level of individual trials, non-rewarded stimuli are more likely to elicit a response when they immediately follow a rewarded trial (in a GNG task). In addition, Busse et al (2011) report that animals tend to switch sides after each trial, regardless of success or failure.…”
Section: Estimating Psychometric Sensitivitymentioning
confidence: 99%
“…For example, monkeys do not make use of all stimulus information available to them, but rather commit to action prior to stimulus termination, thereby ignoring useful information (Roitman and Shadlen, 2002; see also Resulaj et al, 2009). Also, psychophysical performance is frequently not solely determined by sensory processes but by a range of biasing factors, among them recent stimulus and reward history (Boneau et al, 1965; Busse et al, 2011). …”
Section: Introductionmentioning
confidence: 99%